Intracardiac fistula: an unusual complication of catheter-related blood stream infection. (September 2017) - Koratala, Abhilash; Aboud, Hussain; Gibson, Robert; Hamilton, Karen K
Lesson: In end stage renal disease patients on dialysis, the use of catheter as a vascular access is associated with a significant risk of sepsis compared to an arterio-venous fistula. Our case emphasizes the importance of having high index of suspicion for unusual complications in patients presenting with possible catheter-related blood stream infection and early use of complementary tools such as trans-oesophageal echocardiography whenever applicable.